Exploring Sentencing Practice in England and Wales
XVIII, 268 p.
Keywords: This volume explores the theory and practice of sentencing in England and Wales, exploring issues such as the role of previous convictions, offender remorse and sentencing female offenders, as well as drawing upon a new and unique source of data from the Crown courts.